A novel approach to improve the oil miscibility and incorporate multifunctionality in ionic liquids as lubricant additives. Issue 5 (28th January 2021) - Pandey, Priya; Somers, Anthony E.; Hait, Samik K.; Forsyth, Maria; Ramakumar, S. S. V.
Abstract : Recently ionic liquids (ILs) have shown promising tribological properties as additives in base oils; however their lack of miscibility is a problem, with very few ILs being compatible with lubricant oil formulation (non-polar base oils). Abstract : Recently ionic liquids (ILs) have shown promising tribological properties as additives in base oils; however their lack of miscibility is a problem, with very few ILs being compatible with lubricant oil formulation (non-polar base oils). This work shows the use of a surfactant which can increase the range of available ILs that are stable when added to these base oils. In this study a range of tetraalkylphosphonium based ILs were successfully blended with a PIBSA surfactant and these blends were all shown to be miscible in a non-polar base oil. Without the PIBSA a number of the ILs were immiscible in the base oil. The tribological properties of IL additives that are miscible in the non-polar base oils were compared with and without the surfactant present and showed that the presence of the PIBSA did not affect the IL additives performance. Additionally, two ILs that are immiscible without the surfactant showed the greatest reduction in friction and wear. SEM analysis showed an increase in the amount of phosphorus on the wear surface when the surfactant was present, suggesting that the PIBSA enhances tribo-film formation. NMR, FTIR, DLS and TEM investigations into the interactions between the PIBSA and the ILs showed that the improved stability in the base oil may be due to intermolecular interactions such as hydrophobic, van der Waals, dipole–dipole or ion–dipole that reduce the size distribution of the previously immiscible ILs. The presence of the ILs was also shown to improve the resistance to corrosion. Prior to this study the ILs available for use as lubricant additives was severely limited and compromised, mostly based upon their miscibility. Here the use of PIBSA to increase the range of ILs available as lubricant additives has vastly improved the promise that they represent in this area.